Hospital Fire Risk Analysis with Hazard, Vulnerability, Capacity, Risk Assessment Model (KEMAS: Jurnal Kesehatan Masyarakat, 2019)
The purpose of this research is to analyze fire risk level on the hospital in Ponorogo. Hospital is a community health service instantion should be kept away from fire disaster since many of the patients are vulnerable to become the victim. This research is descriptive – analytic with semi-quantitative approach. The scope involves 27 service units on Ponorogo Regional Hospital. Fire risk is analyzed by proportioning and scoring method of hazard, vulnerability and capacity identification result. The research results indicate 18.5% service unit of Ponorogo Regional Hospital has high fire risk. 59.3% medium risk, and 22.2% low risk. The existance of service unit with high fire risk is caused by hazard potential that does not well managed and fire protection systems that do not comply with the standard. The research result is expected to be used as reference in fire protection system improvement on Ponorogo Regional Hospital so that the fire risk can be minimalized.